FACTORS AFFECTING JAMA'AH'S ATTACHMENT WITH ISLAMIC STUDIES GROUP - Ahmad Misbahul Anam (Program Studi Pengembangan Masyarakat Islam STID Mohammad Natsir, 2023)
Majlis Taklim with its role as a place to study also a place to carry out social activities is important for its existence in a socio-religious context. The stability of institutions and programs is sometimes an interesting thing to be studied more deeply. This study aims to examine the factors that have caused the study at the Majlis Taklim at mushala at-Taqwa still run well for the last 15 years. This study used a qualitative descriptive approach with data collection through observation, interviews, and documentation studies. Datas that has been collected is analyzed descriptively by condensing data, presenting data, and conclusions. The results of this study are expected to be a reference for majlis taklim that are managing majlis taklim so that their management is better.